Persepsi Mahasiswa terhadap Metode Pembelajaran Blended Learning dengan Aplikasi Whatsapp Group pada Mahasiswa Insud Lamongan - Pusvyta Sari; Luthfah Nur Aini; Ahsanti Fiqhiyati Putri; Rida Anastashfiya Ghozali (Program Studi Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat Lamongan, 2020)
Perception describes attitude or personal response to the situation and experience gained. This study aims to determine student perceptions of blended learning methods by using the whatsapp group application. This is evaluation research on the components of the use of learning method. The results showed that students perceptions about blended learning using whatsapp group are good. This perception is influenced by personal condition, situational factors and attention to the learning program. Personal factors related to the characteristics of students in communicating and learning. A situational factor is influenced by students activities and regulation on the use of communication devices in their boarding school. The attention to lectures is shown by participation in the group discussion, their hopes to the development of this blended learning method, the enrichment of material through online learning media to optimizing the use of whatsapp group for learning in the higher education Sunan Drajat Boarding School .